1995
DOI: 10.1055/s-2007-972957
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Oxygen Uptake, Stroke Rate and Swimming Velocity in Competitive Swimming

Abstract: The purpose of this study was to determine the relationship between oxygen demand, stroke rate and swimming velocity in competitive swimmers. The subjects who volunteered for this study were ten trained male swimmers (age, 16.7 +/- 0.4 yrs). VO2peak, swimming velocities at 80% (V80% VO2peak) and 100% (V100% VO2peak) of VO2peak and swimming velocity at the onset of blood lactate accumulation (VOBLA) were determined during a swimming economy profile test in a swimming flume. In the swimming economy test, determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
2
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 5 publications
11
83
2
3
Order By: Relevance
“…SF increased with velocity, in contrast to the case for SL, which remained constant. This result confirmed those of previous studies (Holmer (1974;Klentrou and Montpetit (1992;Wakayoshi et al (1995) in which it was demonstrated that SF increased with velocity. Despite the fact that the increase in SF was certainly associated with an increase in muscular activities, in the present study no correlation was found between the swimmers' Cs and stroke parameters such as SL and SF, regardless of the velocity.…”
Section: Influence Of Velocity On _ V V O 2 Cs and The Stroke Paramsupporting
confidence: 93%
See 2 more Smart Citations
“…SF increased with velocity, in contrast to the case for SL, which remained constant. This result confirmed those of previous studies (Holmer (1974;Klentrou and Montpetit (1992;Wakayoshi et al (1995) in which it was demonstrated that SF increased with velocity. Despite the fact that the increase in SF was certainly associated with an increase in muscular activities, in the present study no correlation was found between the swimmers' Cs and stroke parameters such as SL and SF, regardless of the velocity.…”
Section: Influence Of Velocity On _ V V O 2 Cs and The Stroke Paramsupporting
confidence: 93%
“…For a given velocity, the lower Cs was not linked to a lower SL or SF. Similar observations were made by Wakayoshi et al (1995), who concluded that subjects with a greater SL did not spend necessarily less metabolic power. It could be assumed that in swimming as well as in running, each subject chose the optimal SF to minimise the energy expenditure and/or to optimise the performance according to his muscular and anthropometric characteristics (Craig and Pendergast 1979;Kaneko et al 1987).…”
Section: Influence Of Velocity On _ V V O 2 Cs and The Stroke Paramsupporting
confidence: 81%
See 1 more Smart Citation
“…It has been empirically demonstrated that energy expenditure in swimming increases with the swimming velocity cubed (Wakayoshi et al 1995). Theoretically, the mechanical work done to overcome drag by the swimmer per unit of time equals A d ·v, and given that A d =k Ad ·v 2 the swimming intensity should be proportional to k Ad ·v 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Stroke length has been shown to be a major factor determining maximal or submaximal performance in swimming (Keskinen et al 1989;Wakayoshi et al 1995).…”
Section: Cs Versus Swimming Techniquementioning
confidence: 99%